The Role Of Organizational Leadership In Applying Of Knowledge Management Processes "A Field Study At Tishreen University " - البهلول علي (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The research sought to examine the relationship between organizational leadership on the one hand, and between knowledge management processes in Tishreen University on the other hand, where the researcher distributed a questionnaire to a sample of the colleges in the University of Tishreen reached (215) questionnaire, since that(152) responses were received, and(122) questionnaire were used in the analysis(response rate 80%). To test the relationship, the researcher used the Student T test for one sample, as well as the Pearson correlation coefficient. The research concluded that there is a decrease in the level of organizational leadership effectiveness in colleges under study, as well as a decrease in the level of each of the participating and storage of knowledge (knowledge management dimensions) in colleges under study. The research concluded that there is significant relationship between organizational leadership and knowledge management processes at Tishreen University, and thus the existence of the role of organizational leadership in the success of knowledge management processes at Tishreen University. The research found a set of recommendations and proposals that will contribute positively in the role of organizational leadership in the success of knowledge management processes.